Patriarchalic Tradition in Usage of Kinship Terms in Lithuanian and Hindi Languages - Ranjan, Rasa (Acta Orientalia Vilnensia, 2002)
This paper analyses the systems of kinship terms (KT) of two languages - Lithuanian and Hindi. Systematic analysis of KT in different Indo-European languages opens a possibility for comparative - typological study. which allows better understanding of family structure and kinship relations of different ethnic groups. The main goal here is to examine influence of patriarchal family traditions on formation and usage of KT in Lithuanian and Hindi. The historic-comparative method of study is mainly used in this paper. Functionally KT were studied in communication process. Today. when modern society experiences alienation, estrangement in kinship relations, and lack of respect for elderly people, research of KT is relevant not only in comparative linguistics and sociolinguistics but also in education of language culture.